2005
DOI: 10.1179/136485905x51490
|View full text |Cite
|
Sign up to set email alerts
|

Tick modulation of the in-vitro expression of adhesion molecules by skin-derived endothelial cells

Abstract: As a tick feeds, its saliva induces innate and acquired immune responses in the host, including leucocyte infiltration into the bite site. Tick salivary glands produce molecules, however, that counteract many host defences against blood feeding. The effects of salivary-gland extracts (SGE) of Dermacentor andersoni and Ixodes scapularis on the expression of various adhesion molecules [E-selectin, P-selectin, intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1)] by the sEND.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Tick transmitted pathogens have exploited these changes for their own survival. I. scapularis salivary gland extract down-regulates the expression of endothelial cell adhesion molecules P-selectin and vascular cell adhesion molecule-1 that can reduce leukocyte extravasation into dermal tissue (Maxwell et al 2005). These observations help explain the presence of a cell-free zone adjacent to the tick hypostome that we noted after initial tick exposure in mice and human subjects.…”
Section: Discussionsupporting
confidence: 49%
“…Tick transmitted pathogens have exploited these changes for their own survival. I. scapularis salivary gland extract down-regulates the expression of endothelial cell adhesion molecules P-selectin and vascular cell adhesion molecule-1 that can reduce leukocyte extravasation into dermal tissue (Maxwell et al 2005). These observations help explain the presence of a cell-free zone adjacent to the tick hypostome that we noted after initial tick exposure in mice and human subjects.…”
Section: Discussionsupporting
confidence: 49%
“…In fact, tick saliva contains molecules that prevent complement activation (32) and T cell proliferation (13,15,33), and that polarize T cell responses to a Th2 profile (34). Tick saliva also modulates cytokine production by epidermal cells (35) and alters expression of adhesion molecules by skin-derived endothelial cells (36). More recently, a study demonstrated that saliva from R. sanguineus inhibits differentiation, maturation, and cytokine synthesis of bone marrow-derived DCs (20).…”
Section: Discussionmentioning
confidence: 99%
“…A Cu/Zn superoxide dismutase (SOD1) was shown to reduce expression of vascular cell adhesion molecule-1 and mucosal addressin cell adhesion molecule-1 in a mouse experimental model of inflammatory bowel disease (IBD) (Segui et al, 2005). It would be tempting to speculate a similar function of the tick protein since ticks are known to modulate the expression of adhesion molecules such as LFA-1 and Mac-1 on neutrophils (Montgomery et al, 2004) and ICAM-1, P-selectin and VCAM-1 on mouse endothelioma cells derived from skin (Maxwell et al, 2005). However, no signal sequence was identified in the tick gene indicating a more likely role in detoxification of metabolic products.…”
Section: Housekeeping Genesmentioning
confidence: 97%